Carcinoma mammae v puerperiu - Sviteková, M; Minár, L; Pacovský, Z (Klinicka onkologie, 2008)
AIM: This case study reports an occurence of a mammary gland carcinoma in woman during her pregnancy and puerperium. CASE REPORT: Patient was 29 years old woman, without any familiar or personal history of cancer or cancer risk factors. There was a finding of palpable resistance in the lateral superior quadrant of right breast in 30 week of gestation, which was considered to be hormonal changes in pregnancy. The third day after delivery a breast ultrasonography was performed because of persisting mastodynia, moderate oedema in described area and resistance nonresponding to the typical finding in period of incipient lactation. The result was suspicious of tumor. The core cut biopsy revealed invasive ductal carcinoma grade 3 and the staging was determinated as T4b N2 M1 (liver). Because of the high clinical stage of the disease, primary sugical therapy (modified radical mastectomy) was not indicated and the patient underwent neoadjuvant chemotherapy followed byradiotherapy. There was a control PET scan after the chemotherapy which confirmed only residual tumor in the area of affected breast and no viable tumor cells in the area of the liver. Additional reduction of the primary tumor lesion occured after the radiotherapy. The control examination 3 months after the treatment found the statement of the relapse of disease. At the present time, 14 months after the delivery, the paliative chemotherapy is planned. CONCLUSION: Obstetricians should take care not only for routine examinations of pregnant women, but also of the breast changes and when there are uncertain, they must use appropriate diagnostic methods.
Keywords: nádorové komplikace v těhotenství; nádory prsu; Female; Pregnancy Complications, Neoplastic; Adult; dospělí; Puerperal Disorders; Breast Neoplasms; Pregnancy; Humans; ženské pohlaví; duktální karcinom prsu; lidé; poruchy v puerperiu; těhotenství; Carcinoma, Ductal, Breast